Pyruvate kinase deficiency - Zanella, Alberto (Henry Stewart Talks, 2007)
Structure and function of pyruvate kinase, Genetic characteristics, Clinical, haematological and diagnostic aspects, Relation between molecular defect and disease severity, Treatment options
Updated at 2016/07/31